The Traditional Wedding Feast of the Nias Gunungsitoli Muslim Community: Positive Law Perspective and Maqāṣid Ash-Sharī`ah - Gulo, Hadyan; Syam, Syafruddin; Nurcahaya, Nurcahaya (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
The traditional Nias wedding procession of Gunungsitoli City studied relates to famasao marafule, which is divided into fanema marafule, baru safusi and kofo. Problem formulation: 1). How is the procession of the traditional wedding feast carried out by the Nias Muslim community in Gunungsitoli City? 2). How is the procession of the traditional wedding feast carried out by the Nias Muslim community of Gunungsitoli City from the perspective of positive law? 3). How is the procession of traditional marriage feasts carried out by the Muslim community of Nias Gunungsitoli City from the perspective of maqāṣid ash-sharī`ah? Analysing these problems using positive law and maqāṣid ash-sharī`ah approaches. Perspective of Positive Law, contrary to Article 106 of the Civil Code, contrary to Article 3 of KHI because it does not realise sakīnah, mawaddah and raḥmah. The traditional marriage procession of Nias Muslims in Gunungsitoli City is contrary to Article 34 paragraph (1) and paragraph (2) of Law Number 1 of 1974 concerning Marriage, the marriage procession of famasao marafule (fanema marafule, baru safusi), the husband and wife cannot carry out their obligations, the husband does not want to provide maintenance because his wife does not live with him, while the wife cannot take care of her household because she still lives with her parents. The procession of the traditional Nias marriage ceremony in Gunungsitoli City with the condition that the husband and wife live together implemented by the Nias Muslim community in Gunungsitoli City from the perspective of Maqāṣid ash-Sharī`ah violates ḥiẓhud dīn and ḥifẓul `aql in Maqāṣid ash-Sharī`ah.